2020
DOI: 10.1002/adem.202000179
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photonic Soldering with Sn–58Bi Using Intense Pulsed Light Energy

Abstract: Solders, which are the most commonly used materials in electronic packaging, have been widely used for electrical interconnections. When producing a solder joint, a layer is formed on the contact pad, followed by a reflow process conducted using infrared or thermal energy. This process requires a high‐temperature environment and long heating time. Herein, an advanced approach involving photonic soldering using intense pulsed light (IPL) energy is examined thoroughly. In particular, the relation between the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…TLPS thus is accompanied with a long bonding time [18][19][20]. Many approaches have been employed to accelerate the sintering time such as high-temperature/pressure bonding [19,21,22], incorporation of reactive additives [23][24][25][26], surface modification [27,28], and electric/laser-assisted bonding [29][30][31][32][33][34]. For instance, Ramli et al employed TiO 2 particles to reduce the thickness of the interfacial IMCs for the enhancement of the shear strength and hardness of the solder joints [24].…”
Section: Introductionmentioning
confidence: 99%
“…TLPS thus is accompanied with a long bonding time [18][19][20]. Many approaches have been employed to accelerate the sintering time such as high-temperature/pressure bonding [19,21,22], incorporation of reactive additives [23][24][25][26], surface modification [27,28], and electric/laser-assisted bonding [29][30][31][32][33][34]. For instance, Ramli et al employed TiO 2 particles to reduce the thickness of the interfacial IMCs for the enhancement of the shear strength and hardness of the solder joints [24].…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of documented instances involve the application of IPL soldering to Sn-based solder formulations within operational electronic packages [11][12][13][14][15][16]. Jung et al [11] presented findings detailing the IPL soldering of Sn-58Bi, illustrating a mere 2.5% duration requirement relative to conventional reflow techniques, alongside a 40% enhancement in mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of documented instances involve the application of IPL soldering to Sn-based solder formulations within operational electronic packages [11][12][13][14][15][16]. Jung et al [11] presented findings detailing the IPL soldering of Sn-58Bi, illustrating a mere 2.5% duration requirement relative to conventional reflow techniques, alongside a 40% enhancement in mechanical strength. Ha et al [12] conducted an evaluation of the reliability impact on Sn-3.0Ag-0.5Cu ball grid array (BGA) packages with Electroless Nickel Electroless Palladium Immersion Gold (ENEPIG) surface treatment, employing the IPL soldering methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, most studies have mainly focused on printed electronics, [ 13–16 ] whereas only a few studies on IPL soldering and the reliability of the resulting solder joints have been reported. [ 17–19 ] Herein, we investigated IPL soldering as an alternative technology to reflow soldering. We formed solder joints using Sn–3.0Ag–0.5Cu lead‐free solder (SAC305) and a PCB with an electroless‐nickel/electroless‐palladium/immersion‐gold (ENEPIG) surface finish through IPL soldering.…”
Section: Introductionmentioning
confidence: 99%